The Whole Client: Rethinking Financial Wellness Through Interdisciplinary Practice - Randall Stone; Sarah Stone (Journal of Financial Therapy, 2026)
Financial wellness challenges are increasingly complex and multidimensional, shaped by structural constraints, behavioral frictions, and technical financial decision-making. While interdisciplinary approaches to financial well-being spanning financial social work, personal financial planning, and behavioral economics are already emerging in academic programs and professional associations, practitioners often lack a clear, practice-oriented framework for integrating these perspectives into day-to-day client work. This article offers a practitioner-oriented integrative review that synthesizes these three disciplines into a cohesive practice map for addressing the financial needs of diverse and often marginalized populations. Rather than proposing a novel discipline, the paper clarifies the distinct contributions of each field, identifies points of convergence, and examines persistent barriers to interdisciplinary implementation, including professional silos, credentialing norms, compensation models, and ethical boundaries. The article concludes with practical implications for interdisciplinary service delivery, training, and collaboration, offering a roadmap for practitioners seeking to operationalize a whole-client approach to financial wellness.
Keywords: behavioral economics; financial capability; financial social work; interdisciplinary practice; personal financial planning